O teletrabalho de servidores técnico-administrativos durante a emergência sanitária da COVID-19 em um centro acadêmico da Universidade Federal da Paraíba - Fonseca Júnior, Walter Luiz Rocha da (2023)
The study aims to understand the experience of teleworking exercised by technicaladministrative staff, assigned to the Health Sciences Center of the Federal University of Paraíba, due to the pandemic caused by Covid-19. Although its spread comes from the pandemic context, given the need for preventive measures, such as social isolation, teleworking has been the subject of study since the middle of the last century, motivated by the development of new information and communication technologies. In Brazil, several private and public institutions already practiced teleworking, in whole or in part, before the pandemic. However, the adoption at UFPB was a direct result of the pandemic, through the publication of a general rule that allowed this type of work for as long as the severity and high contagion of the disease persisted. In order to carry out this research, we carried out a bibliographical survey, looking at the origin of teleworking, its concept, its characteristics in publications on the subject, thus pointing out the position of the doctrine on the subject. A documentary survey was also carried out, especially of teleworking legislation, other rules created by the Federal Government aimed at federal civil servants, and specific ones, such as those drawn up by the UFPB. Based on a predominantly qualitative analysis, we sought to understand, through questionnaires, the characterization of teleworking in practice at the institution and its consequences. Therefore, even though the study was carried out in a specific sector of the university, we sought to contribute to the administrative management of its employees, in order to serve as a parameter in future decisions on whether or not to implement teleworking. Finally, as a product of the research, a guidebook on teleworking is presented, based on the main information collected and with the aim of deepening this discussion within the institution.